Design and Analysis of a Highly Reliable Permanent Magnet Synchronous Machine for Flywheel Energy Storage - Xinjian Jiang; Lei Zhang; Fuwang Li; Zhenghui Zhao (Machines, 2024)
This article aims to propose a highly reliable permanent magnet synchronous machine (PMSM) for flywheel energy-storage systems. Flywheel energy-storage systems are large-capacity energy storage technologies suitable for the short-term storage of electrical energy. PMSMs have been used in the flywheel energy-storage systems due to their advantages. One of the key requirements for PMSMs in flywheel energy-storage systems is high reliability. A double redundant winding structure is adopted to ensure fault-tolerant operation of the PMSM. The stator is designed with auxiliary teeth to reduce the short-circuit current. Moreover, the number of slots and poles is determined to ensure the winding factor, heat dissipation, and reduce losses. Moreover, the dual three-phase stator winding structure and auxiliary teeth are adopted on the PMSM to improve reliability. Afterward, the electromagnetic performance is analyzed, and the mechanical stress is investigated to ensure mechanical strength. Finally, a prototype is built and tested to verify the theoretical analysis and performance of the PMSM.